A Novel Hybrid Nested Reverberation Chamber Measurement Technique for Shielding Effectiveness of Conductive Fabrics - Ozdemir, Hakki Ekin; Nisanci, Muhammet Hilmi; Ustuner, Fatih; Citkaya, Ahmet Yasin; Torpi, Hamid; Mersin, Mucahid Taha; Aba, Ridvan; Cosar, Coskun (IEEE, 2022)
This paper presents a novel hybrid nested reverberation chamber measurement technique for shielding effectiveness measurement of the conductive fabrics. The test setup consists of a conventional outer reverberation chamber and a small inner chamber whose walls and ceiling are covered with electromagnetic absorbers. Therefore, the inner chamber which has no stirrer acts as a semi-anechoic chamber, whereas the outer chamber acts as a reverberation chamber (RC) and the proposed test setup shows a hybrid characteristic. In this study, firstly, the field uniformity of the outer RC is experimentally verified considering the IEC 61000-4-21 standard in the frequency range of 2-10 GHz. Afterwards, both the shielding effectiveness of the conductive fabric and the dynamic range of the proposed nested reverberation chamber (NRC) technique are obtained. Moreover, the obtained results are compared with the MIL-DTL-83528G test method.
Keywords: nested reverberation chamber; shielding effectiveness; dynamic range; conductive fabric; Engineering